2013
DOI: 10.1177/0743558413477197
|View full text |Cite
|
Sign up to set email alerts
|

Sunni-Muslim American Religious Development During Emerging Adulthood

Abstract: Islam is one of the fastest growing religions in America, with approximately 6 to 7 million Muslims living in America within the past decade. However, there has been little psychological research conducted focusing on the development of the Muslim American self. This inquiry addresses that gap by focusing on how familial religious affiliation during childhood and the everyday environmental activity systems of emerging adulthood impact religious practice and the construction of the religious self among Sunni-Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…Religious practices are understood to be mediated by individuals in response to variations of their everyday environments, social interactions, and sociopolitical contexts (Belzen, 1999). For example, Etengoff and Daiute (2013) found that their sample of Sunni-Muslim American emerging adults used religious activity systems and artifacts such as the Qu'ran to navigate ethno-religious questions proposed by non-Muslims in post 9/11 contexts, indicating that religious tools can be used to successfully mediate intercultural conflicts (Etengoff & Daiute, 2013). This study expands the current discussion of the sociorelational context of religious development by focusing on how gay men and their religious family members utilize religion to defend their positions, reconcile conflicts, and mediate familial relationships in post-coming-out contexts.…”
Section: Cultural Historical Activity Theory and Religionmentioning
confidence: 99%
See 2 more Smart Citations
“…Religious practices are understood to be mediated by individuals in response to variations of their everyday environments, social interactions, and sociopolitical contexts (Belzen, 1999). For example, Etengoff and Daiute (2013) found that their sample of Sunni-Muslim American emerging adults used religious activity systems and artifacts such as the Qu'ran to navigate ethno-religious questions proposed by non-Muslims in post 9/11 contexts, indicating that religious tools can be used to successfully mediate intercultural conflicts (Etengoff & Daiute, 2013). This study expands the current discussion of the sociorelational context of religious development by focusing on how gay men and their religious family members utilize religion to defend their positions, reconcile conflicts, and mediate familial relationships in post-coming-out contexts.…”
Section: Cultural Historical Activity Theory and Religionmentioning
confidence: 99%
“…
Religion often creates cultural meaning for interpersonal relations as individuals and societies develop interactively (Etengoff & Daiute, 2013). Religious tools, such as God and texts, have reportedly been used in both relationally adaptive and maladaptive ways (Brelsford & Mahoney, 2009;Brelsford, 2011).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the institution of the family should be aware of the importance of religious education to their children since they were at young. As argued by Etengoff and Daiute (2013) that there has been little psychological research conducted focusing on the development of the Muslim American self, with approximately 6 to 7 million Muslims living in America within the past decade. This inquiry addresses that gap by focusing on how familial religious affiliation during childhood and the everyday environmental activity systems of emerging adulthood impact religious practice and the construction of the religious self among Sunni-Muslim American emerging adults (N = 63, 18-29 years) via the development of diverse mediational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the task of families and individuals engaging conflicting religious and sexual practices is to define and mediate the relation between these activity systems. Within this sociocultural perspective, mediation is understood as "the use of language and other symbol systems to perceive, manage, and develop self-society relations" (Daiute, 2010, p. 48) and is thus studied by focusing the unit of analysis on individuals' relational uses of sociohistorically constructed and individually adapted physical, symbolic, or abstract cultural tools (Etengoff & Daiute, 2013). Although this theoretical paradigm has yet to be deliberately applied to the research design and analysis of the population studied in this article, Pargament (1999, p. 176) has developed the complementary paradigm of spiritually integrated therapy, which "assumes that spirituality is often interwoven with the problems clients bring to psychotherapy, the solutions to these problems, and the clients' larger social and cultural context."…”
Section: Cultural Historical Activity Theory and Relational Complexitymentioning
confidence: 99%